Code of Conduct for Appropriate Punishment of Children in Islamic Education - Pela Safni (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
This research aims to analyze the code of ethics for punishing children appropriately in Islamic education. The main focus is what are the types of punishment and what are the conditions for applying a punishment to children by parents/educators. The method used in this study is library research. Literature research aims to collect, review, and analyze relevant data and information from various credible and valid literature sources.Related to the code of ethics for punishing children appropriately in Islamic education. The results of the study show that there are 7 types of punishment for children, namely: 1) Advice, direction, and warning; 2) Turn away; 3) Sour face; 4) Prevention; 5) Stopping an act; 6) Boycott; and 7) Display sticks. In addition, there are 9 codes of ethics in the application of punishment to children, such as giving warnings, carrying out punishment directly, providing opportunities to calm down and calmness when giving punishment. Avoid using threatening language, make sure the punishment does not last long, and do the punishment without spectators that can make the child feel embarrassed or inferior. Spanking is applied only as a therapy for scratching, not as a form of punishment that is harsh or degrading to the dignity of the child